Interdisciplinarity in education for sustainable development: business schools perspectives - Martins, Flavio Pinheiro (2021)
Business Schools play an essential role in sustainable development agenda integration since their practices are vectors for a needed paradigm change. Nevertheless, they are often criticized for not forming the actors of change towards a sustainable future. Interdisciplinarity can aid the development of systemic patterns able to grasp the Education for Sustainable Development (ESD) complexity. This work addresses ESD in the school\'s signatories of the Principles for Responsible Management Education (UN-PRME): an educational platform developed to aid the business schools. Research is framed through the lens of critical and instrumental interdisciplinarity perspectives and is summarized in the question: How interdisciplinary linkages to Education for Sustainable Development in Business Schools? Methods rely on the evaluation of 37 PRME Schools Reports and interviews with educators. Results are analyzed through content analysis, supported by text-mining and network theory tools. The primary outcomes are I) a review with a future research agenda, II) a taxonomy of critical and instrumental Interdisciplinarity, and III) a framework of the PRME schools. The results contribute theoretically with advancing research on the intermesh of ESD, Responsible Management Education, and Interdisciplinarity. The developed framework is a tool for diagnosis and prognosis on how interdisciplinary can improve ESD in business schools.